UPAYA MENINGKATKAN KEMAMPUAN MEMBACA DAN MEMIRSA MELALUI MEDIA DISPLAY PADA MATERI MENGENAL HURUF ABJAD - Abdullah, Tarisa T; Jusuf, Harni; Pratiwi, Wiwik (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
This research aims to improve the reading and viewing skills of grade 2 students at SDN 1 Limboto Barat on material about recognizing the alphabet. The problem identified was the low reading and viewing ability of students, where around 12 students had not reached the Minimum Completeness Criteria (KKM). To overcome this problem, this research applies display media as a learning aid. The method used in this research is Classroom Action Research (PTK) which involves four main stages: observation, planning, action, and reflection. At the observation stage, researchers identify students' problems and needs. The planning stage involves preparing learning strategies using display media. The action stage involves implementing the plans that have been prepared, while the reflection stage is used to evaluate the effectiveness of the actions taken. Data is collected through observation and tests. The results showed significant improvements in students' reading and viewing abilities. Before the action, only 44.44% of students reached the KKM. However, after using display media, the percentage of students who achieved the KKM increased to 84.71%. Based on these results, it can be concluded that the use of display media is effective in improving the reading and viewing abilities of grade 2 students at SDN 1 Limboto Barat. This research makes a positive contribution to efforts to improve the quality of learning, especially in material about recognizing the alphabet, and can be used as a reference for teachers in implementing innovative learning strategies.